ALMA polarization observations of the particle accelerators in the hotspot of the radio galaxy 3C 445. (1st May 2017) - Orienti, M.; Brunetti, G.; Nagai, H.; Paladino, R.; Mack, K.-H.; Prieto, M. A.
Abstract: We present Atacama Large Millimeter Array polarization observations at 97.5 GHz of the southern hotspot of the radio galaxy 3C 445. The hotspot structure is dominated by two bright components enshrouded by diffuse emission. Both components show fractional polarization between 30 and 40 per cent, suggesting the presence of shocks. The polarized emission of the western component has a displacement of about 0.5 kpc outward with respect to the total intensity emission and may trace the surface of a front shock. Strong polarization is observed in a thin strip marking the ridge of the hotspot structure visible from radio to optical. No significant polarization is detected in the diffuse emission between the main components, suggesting a highly disordered magnetic field likely produced by turbulence and instabilities in the downstream region that may be at the origin of the extended optical emission observed in this hotspot. The polarization properties support a scenario in which a combination of both multiple and intermittent shock fronts due to jet dithering and spatially distributed stochastic second-order Fermi acceleration processes are present in the hotspot complex.